The Role of Digital Communication in Enhancing a Company's Competitive Advantage - Muhamad Bagas Julio; Saprida Saprida; Fadilla Fadilla; Havis Aravik; Ahmad Tohir (TOMAN: Jurnal Topik Manajemen, 2026)
Business communication in the digital era has undergone changes due to the rapid development of information and communication technology. The purpose of this explanation is to examine how digital communication contributes to increasing a company's competitive advantage. This research uses a conceptual and empirical approach. This study employed a qualitative method with a literature review design and focused on scientific journal articles published between 2020 and 2025. The results show that digital communication helps strengthen brand image, disseminate information more quickly, and build better stakeholder relationships. Companies can reach a wider market more effectively through digital platforms such as social media, company websites, and digital marketing tools. Integrated digital communication also improves organizational responsiveness, customer loyalty, and innovation capacity. According to this study, businesses that strategically use digital communication will gain a more sustainable competitive advantage in the increasingly global marketplace.